'We've made the best of it. But we do not have a normal life': families' experiences of tuberous sclerosis complex and seizure management. Issue 8 (18th February 2019) - McDonald, A.; Goodwin, J.; Roberts, S.; Fish, L.; Vaughan, B.; Cooper, A.; Cadwgan, J.
Abstract: Background: Tuberous sclerosis complex (TSC) is a complex multisystem genetic disorder. Approximately 84% of people with TSC have epilepsy. However, there is little literature available regarding families' experiences with TSC and seizure management. Therefore, the aim of the current study was to explore families' positive and negative experiences, and attitudes towards TSC, epilepsy and medical management of seizures. Methods: Framework analysis informed an open exploration of families' experiences with TSC, epilepsy and medical management of seizures. Using structured interviews, 11 parents of people with TSC and 2 people with TSC were interviewed, providing the data set for transcription and thematic analysis. Results: 'TSC rules our life' overarched three subordinate themes: 'Our normal', 'Burnout' and 'Seizure management has given us our life back'. Families had to adapt to the normality of needing to constantly supervise their child even as they become an adult. They express a feeling of fear particularly of seizures, and this has impact throughout the family. There are frequent expressions of exhaustion and struggling to fight for access and support. There are some positives and cautious hope with the gaining of control from seizures as being able to predict or plan improves activity and participation. These interviews provided a rich insight into the lives of those with TSC and their families. Conclusion: There are exciting developments with respect to scientific understanding of the pathophysiology of TSC, which opens opportunity for new treatments. Holistic family centred health care and practical support (e.g. opportunities for parental respite) is as important as medical intervention. As TSC is such a complex condition, there is a need for specialist clinics and TSC‐specific research.